Verification Testing to Confirm VO2max in Altitude-Residing, Endurance-Trained Runners - Weatherwax, R. M.; Richardson, T. B.; Beltz, N. M.; Nolan, P. B.; Dalleck, L. (International Journal of Sports Medicine, 2016)
We sought to explore the utility of the verification trial to confirm individual attainment of ‘true’ VO2max in altitude-residing, endurance-trained runners during treadmill exercise. 24 elite endurance-trained men and women runners (age=21.5±3.3 yr, ht=174.8±9.3 cm, body mass=60.5±6.7 kg, PR 800 m 127.5±13.1 s) completed a graded exercise test (GXT) trial (VO2max=60.0±5.8 mL·kg−1·min−1), and returned 20 min after incremental exercise to complete a verification trial (VO2max=59.6±5.7 mL·kg−1·min−1) of constant load, supramaximal exercise. The incidence of ‘true’ VO2max confirmation using the verification trial was 24/24 (100%) with all participants revealing differences in VO2max≤3% (the technical error of our equipment) between the GXT and verification trials. These findings support use of the verification trial to confirm VO2max attainment in altitude-residing, endurance-trained runners.
Keywords: maximal oxygen uptake; incremental exercise test; true VO2max; verification phase; VO2 plateau; hypoxia